Anti‐FIRΔexon2, a splicing variant form of PUF60, autoantibody is detected in the sera of esophageal squamous cell carcinoma. Issue 6 (20th May 2019) - Kobayashi, Sohei; Hiwasa, Takaki; Ishige, Takayuki; Rahmutulla, Bahityar; Kano, Masayuki; Hoshino, Tyuji; Minamoto, Toshinari; Shimada, Hideaki; Nomura, Fumio; Matsubara, Hisahiro; Matsushita, Kazuyuki
Abstract: Anti‐PUF60 autoantibodies are reportedly detected in the sera of patients with dermatomyositis and Sjögren's syndrome; however, little is known regarding its existence in the sera of cancer patients. FIR, a splicing variant of the PUF60 gene, is a transcriptional repressor of c‐myc . In colorectal cancer, there is an overexpression of the dominant negative form of FIR, in which exon 2 is lacking (FIRΔexon2). Previously, large‐scale SEREX (serological identification of antigens by recombinant cDNA expression cloning) screenings have identified anti‐FIR autoantibodies in the sera of cancer patients. In the present study, we revealed the presence and significance of anti‐FIR (FIR/FIRΔexon2) Abs in the sera of patients with esophageal squamous cell carcinoma (ESCC). Our results were validated by an amplified luminescence proximity homogeneous assay using sera of patients with various cancer types. We revealed that anti‐FIRΔexon2 Ab had higher sensitivity than anti‐FIR Ab. Receiver operating characteristic (ROC) analysis was applied for evaluating the use of anti‐FIRΔexon2 Ab as candidate markers such as anti‐p53 Ab and carcinoembryonic antigen, and the highest area under the ROC curve was observed in the combination of anti‐FIRΔexon2 Ab and anti‐p53 Ab. In summary, our results suggest the use of anti‐FIRΔexon2 Ab in combination with the anti‐p53 Ab as a predictive marker for ESCC. The area under the ROC curve was further increased in the advanced stage of ESCC. The value of anti‐FIRΔexon2 autoantibody as novel clinical indicator against ESCC and as a companion diagnostic tool is discussed. Abstract : In summary, our results suggest that the combination of anti‐FIRΔexon2 Abs with anti‐p53 Ab is a potential approach for the diagnosis of esophageal squamous cell carcinoma (ESCC). The area under the receiver operating characteristic curve (ROC) was further increased in the advanced stage of ESCC patients.